Defective IL-10 expression and in vitro steroid-induced IL-17A in paediatric severe therapy-resistant asthma. Issue 6 (17th December 2013) - Gupta, Atul; Dimeloe, Sarah; Richards, David F; Chambers, Emma S; Black, Cheryl; Urry, Zoe; Ryanna, Kimuli; Xystrakis, Emmanuel; Bush, Andrew; Saglani, Sejal; Hawrylowicz, Catherine M
Abstract : Background: Understanding of immune mechanisms underpinning asthma has emerged from studies in adults. It is increasingly recognised, both immunologically and in the development of novel therapies, that adult responses cannot be used accurately to predict those of children. Methods: Using a well-defined paediatric cohort of severe therapy-resistant asthma (STRA) patients, we investigated cytokine profiles in the airway by analysis of bronchoalveolar lavage fluid. The in vitro capacity of peripheral blood mononuclear cells (PBMCs) for cytokine production was also assessed following polyclonal T cell activation in culture, in the absence or presence of dexamethasone and 1α, 25-dihydroxyvitamin D3. Results: Children with both moderate and STRA had significantly diminished levels of anti-inflammatory interleukin (IL)-10 in airway lavage samples when compared with non-asthmatic controls (p<0.001). Their PBMCs also demonstrated significantly impaired capacity to secrete IL-10 in culture (p<0.001). Dexamethasone regulated the balance between PBMC IL-10 and IL-13 production, increasing IL-10 secretion (p<0.001) and decreasing IL-13 (p<0.001) but unexpectedly enhanced IL-17A production in all groups—most strikingly in the STRA cohort (p<0.001). The inclusion of the active form of vitamin D, 1α, 25-dihydroxyvitamin D3, in culture enhanced dexamethasone-induced IL-10 (p<0.05) without marked effects on IL-13 or IL-17A production. Furthermore, systemic vitamin D status directly correlated with airway IL-10 (r=0.6, p<0.01). Conclusions: These findings demonstrate reduced peripheral and local IL-10 synthesis in paediatric asthma, and support therapeutic augmentation of low circulating vitamin D in severe, difficult-to-treat asthma, in order to correct impaired IL-10 levels. Conversely, steroids enhanced IL-17A levels, and therefore any steroid-sparing properties of vitamin D may have additional benefit in STRA.